A study on anxiety level of foreign language students toward foreign language learning - Wan Zakaria, Wan Zarina; Hashim, Nur-Al Huda; Rajab, Azizah; Zaini, Dzulkarnain (Faculty of Management and Human Resource Development, 2005)
A study was conducted to determine and compare the perceptions of University Teknologi Malaysia students towards the feeling of anxiety they experienced when learning the foreign language. Specifically, the objective of the study was to investigate and compare the perception of two groups of students taking the foreign language subject based on of the factors that contribute to the feeling of anxiety. Among the factors studied were communication apprehension, fear of negative evaluation, general feeling of anxiety and overall anxiety. Numerous variables that may affect the level of anxiety such as the students course, gender and race were studied. The instrument used for the survey was adapted from Horwitzs (1983) questionnaire. This Foreign Language Classroom Anxiety Scale (FLCAS) was designed to measure the levels of anxiety experienced by the foreign language students based on performance-related tasks. The questionnaire contained 33 items, each one on a 5-point Likert scale ranging from strongly agree? (point 1 scale) to strongly disagree? (point 5 scale). The data obtained were analyzed using SPSS version 10.0 Windows and were represented in the form of descriptive statistics which include percentages, mean, t-score, one-way analysis of variance (ANOVA) and the Least Significant Diffrence (LSD). The findings of the study indicate that students experienced some levels of anxiety in response to some aspects of foreign language learning. For the overall anxiety, Chinese and Malay students showed a higher level of anxiety compare with the Indian and other races students.